1993
DOI: 10.1073/pnas.90.5.1932
|View full text |Cite
|
Sign up to set email alerts
|

Glucokinase mutations associated with non-insulin-dependent (type 2) diabetes mellitus have decreased enzymatic activity: implications for structure/function relationships.

Abstract: The glycolytic enzyme glucokinase plays an important role in the regulation of insuln secretion and recent studies have shown that mutations in the human glucokinas gene are a common cause of an autosomal domint form of non-inssulin-dependent (type 2) diabetes meilitus (NIIDDM) that has an onset often during childhood. The majority of the mutations that have been identified are missense mutations that result in the syntheis of a glucokinas molecule with an altered amino acid sequence. To characterize the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
106
4
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(116 citation statements)
references
References 25 publications
4
106
4
1
Order By: Relevance
“…3), our results showed that the R308W mutation had significant effects on both K cat and affinity for glucose. Previous studies have reported that another MODY2 mutation in a contiguous amino acid (L309P) results in a similar negative effect on K cat and on substrate affinities [16,33]. Thus, this result further supports the idea that this region of the protein could be involved in the affinity of the enzyme for glucose.…”
Section: Discussionsupporting
confidence: 82%
“…3), our results showed that the R308W mutation had significant effects on both K cat and affinity for glucose. Previous studies have reported that another MODY2 mutation in a contiguous amino acid (L309P) results in a similar negative effect on K cat and on substrate affinities [16,33]. Thus, this result further supports the idea that this region of the protein could be involved in the affinity of the enzyme for glucose.…”
Section: Discussionsupporting
confidence: 82%
“…GK is a key regulator in the hepatic control of glucose storage and disposal [6,24]. Since GK gene expression was decreased in some diabetic patients [8,9,10], increasing GK activity in the liver appeared as an attractive approach to normalize hyperglycaemia, a common feature of both Type I and Type II diabetes. Hyperglycaemia is the main factor responsible for the development of diabetes-associated retinal, renal, neurological and vascular complications [25].…”
Section: Discussionmentioning
confidence: 99%
“…Studies focused on GK gained particular attention since the discovery that MODY-2 is associated with mutations in the GK gene resulting in reduced GK activity in both liver and beta cells [8,9]. Lower hepatic GK activity was also reported in a group of patients with Type II (non-insulin-dependent) diabetic mellitus patients [10].…”
mentioning
confidence: 99%
“…2). They have been found in subjects of many different racial and ethnic backgrounds including Caucasians (Brazil [this report], France [4,10,11], Italy [20], Sweden [21], Switzerland [22], United Kingdom [23], and United States [24] ), Asians (Japan [15,16,25] ), blacks (Congo [11] ), and admixed populations (African-American [21,26] and Puerto Rican [24] ). The majority of the mutations identified to date have been described in only a single family suggesting that the present list is not exhaustive and that new mutations will continue to be found.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the mutations identified to date have been described in only a single family suggesting that the present list is not exhaustive and that new mutations will continue to be found. Those mutations found in more than one family include V182M (two French families [4] ), R186X (two French [11 and this report], one Japanese [15], and one Black-African family [11] ), A188T (one Japanese [25] and one Italian family [20] ), V203A (one French [4] and four Swiss families [22] suggesting a possible founder effect in Switzerland), G261R (three French [4 and this report] and one Japanese family [16] ), E279Q (two African-American families [21] ), and G299R (two British families with a possible founder effect in Oxfordshire [23] ). Our previous studies have shown that missense mutations have variable effects on glucokinase activity ranging from a small change in affinity for glucose to complete inactivity [21,[27][28][29].…”
Section: Discussionmentioning
confidence: 99%